2021
DOI: 10.1158/2159-8290.cd-21-0331
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Biomarker Analysis of Combined PD-L1 (Atezolizumab) and VEGF (Bevacizumab) Blockade in Advanced Malignant Peritoneal Mesothelioma

Abstract: Malignant peritoneal mesothelioma (MPeM) is a rare but aggressive malignancy with limited treatment options. VEGF inhibition enhances efficacy of immune-checkpoint inhibitors by reworking the immunosuppressive tumor milieu. Efficacy and safety of combined PD-L1 (atezolizumab) and VEGF (bevacizumab) blockade (AtezoBev) was assessed in 20 patients with advanced and unresectable MPeM with progression or intolerance to prior platinum–pemetrexed chemotherapy. The primary endpoint of confirmed objective response rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 32 publications
(19 reference statements)
2
33
0
Order By: Relevance
“…Several studies have demonstrated that ICI and anti-angiogenic agent combination therapy has synergistic antitumor activity in solid tumors (8)(9)(10). The vascular endothelial growth factor (VEGF) has pleiotropic immunosuppressive effects including impairment of dendritic cell function, as well as mobilization of immunosuppressive cells such as myeloid-derived suppressor cells, regulatory T cells, and tumor associated macrophages (11).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that ICI and anti-angiogenic agent combination therapy has synergistic antitumor activity in solid tumors (8)(9)(10). The vascular endothelial growth factor (VEGF) has pleiotropic immunosuppressive effects including impairment of dendritic cell function, as well as mobilization of immunosuppressive cells such as myeloid-derived suppressor cells, regulatory T cells, and tumor associated macrophages (11).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the equivalence of chemotherapy and ipi-nivo in E-MPM, it can be argued that post platinum-doublet immunotherapy could be considered a reasonable treatment option at this time based on phase 3 evidence particularly in settings where bevacizumab and chemotherapy are available in the first-line setting. With the emergence of apparently synergistic immunotherapy combinations in the relapsed setting, 13 an alternative algorithm extending beyond CONFIRM could further improve survival of patients with E-MPM. It is unknown whether previous platinum therapy could prime mesotheliomas to benefit from immunotherapy; however, based on models of Sting-GAS pathway activation involving DNA damaged mediated cytosolic DNA sensing and resulting immune cell tumor infiltration.…”
Section: Sequential Immunotherapymentioning
confidence: 99%
“…Next-generation sequencing (NGS) failed due to inadequate specimen; therefore, we could not assess tumor mutational burden (TMB). Because of a negative PD-L1 status, we did not use PD-L1 inhibitors [ 5 ]. After one cycle of IV chemotherapy, the first PET/CT was obtained to evaluate disease burden and for management planning, which revealed FDG avidity of the thickened peritoneum and pleural-based nodules along the diaphragm ( Figure 8 ).…”
Section: Case Reportmentioning
confidence: 99%